Endorobots for Colonoscopy: Design Challenges and Available Technologies - Manfredi, Luigi (Frontiers in Robotics and AI, 2021)
Colorectal cancer (CRC) is the second most common cause of cancer death worldwide, after lung cancer (Sung et al. 2021). Early stage detection is key to increase the survival rate. Colonoscopy remains to be the gold standard procedure due to its dual capability to optically inspect the entire colonic mucosa and to perform interventional procedures at the same time. However, this causes pain and discomfort, whereby it requires sedation or anaesthesia of the patient. It is a difficult procedure to perform that can cause damage to the colonic wall in some cases. Development of new technologies aims to overcome the current limitations on colonoscopy by using advancements in endorobotics research. The design of these advanced medical devices is challenging because of the limited space of the lumen, the contorted shape, and the long tract of the large bowel. The force applied to the colonic wall needs to be controlled to avoid collateral effects such as injuries to the colonic mucosa and pain during the procedure. This article discusses the current challenges in the colonoscopy procedure, the available locomotion technologies for endorobots used in colonoscopy at a prototype level and the commercial products available.